Urgensi Amandemen Kelima Undang-Undang Dasar 1945 di Masa Pandemi - Galuh Candra Purnamasari (Penerbit Goodwood, 2023)
Purpose: The issue of the limited amendment to the 1945 Constitution (UUD 1945) was rolling again during the unfinished pandemic in Indonesia. The idea to carry out the limited amendment to the 1945 Constitution on a limited basis was in line with the issue of extending the Presidential term to three terms and the issue of adding the authority of the MPR to form the Basic Principles of State Policy (PPHN). Conceptually, it is possible to amend the 1945 Constitution as the constitution of the State of Indonesia. However, the problem that arises is whether the amendment to the 1945 Constitution is something that is very important and urgent to be carried out at this time, especially when Indonesia is still in a pandemic condition? To answer these problems, this study intends to explain the concept of amendments to the 1945 Constitution and analyze the urgency of implementing the amendments to the 1945 Constitution during this pandemic. Method: This paper uses library method with secondary data in the form of library materials as the main data. Result: The results of the study, there is no important and urgent matters for the implementation of the fifth amendment to the 1945 Constitution during a pandemic, so that the fifth amendment to the 1945 Constitution, especially during the pandemic, is not appropriate to be implemented. Limitations: The limitation of this paper is that it only focuses on the urgency of limited amendments during the pandemic with two main issues. Contribution: The expected contribution of this paper is to provide a legal review of the issue of the limited amendment of the 1945 Constitution during the pandemic.